Seasonal Variability of Trace and Heavy Metals Concentration in Groundwater and its Quality for Drinking and Irrigation Purpose under Phuleli Canal Command Area (Sindh), Pakistan - Ashifa Soomro; Altaf Ali Siyal; Muhammad Saffar Mirjat; Nabi Bux Sial (Journal of Basic & Applied Sciences, 2013)
The availability of good quality groundwater is a serious problem not only for drinking purpose but also for agriculture production. Human health problems due to waterborne diseases are commonly reported in Phuleli Canal Command area. In this context, a study was conducted to find out the existence of heavy metals as well as trace elements in groundwater of Phuleli Canal Command area, (Sindh) Pakistan which were affected by seasonal variability. The groundwater samples were collected from different seven locations i.e. RD-0, RD-30, RD-50, RD-70, RD-90, RD-110 and RD-130 throughout four seasons (summer, autumn, winter, and spring). Results of analysis of groundwater samples showed that Fe, Cd, Cr and Pb concentration in groundwater was higher than WHO permissible limit while Cu and Mn concentrations were greater than FAO limit. Comparatively heavy metals (Cd, Cr, Pb and As) concentrations in groundwater were higher towards downstream reach in winter as compared to upstream reach. Regarding seasons, the values of these parameters decreased in autumn>spring>summer. The results also showed increasing trend of heavy metal concentrations towards downstream reach (RD 130>110>90>70>50>30>0). It was concluded that groundwater in Phuleli Canal Command area contains highly toxic metals above the permissible limits of WHO and FAO for human consumption and agricultural crops respectively. Hence, people using groundwater, directly or indirectly, at downstream reach of the canal are at health risk.